PROSPECTS FOR ENHANCING STUDENTS' CREATIVITY IN BIOLOGY EDUCATION - "Sayyora Abdulboqiyevna To‘xtaboyeva (TADQIQOTLAR, 2025)
Abstract This article elucidates the transformative potential of fostering creativity within biology education, with a particular focus on academic lyceums in Uzbekistan. By integrating  innovative  pedagogical  strategies,  such  as  inquiry-based  learning, interdisciplinary approaches, and project-based methodologies, educators can cultivate students’ creative capacities, enabling them to transcend rote memorization and engage in profound scientific inquiry. The article delineates how creativity enhances critical thinking, problem-solving, and the ability to innovate in biological sciences, which are pivotal  for  addressing  contemporary  challenges  in  Uzbekistan’s  educational  and scientific landscape. Practical examples, including experimental design projects and collaborative  learning  initiatives,  are  explored  to  illustrate  actionable  strategies  for implementation.  This  study  serves  as  an  erudite  guide  for  educators  in  academic lyceums, advocating for a paradigm shift towards creativity-driven biology education to nurture a generation of innovative thinkers equipped to advance scientific discovery and societal progress.